(untitled) (Research, Society and Development, 2022)
Little is known about self-adhesive flowable composite resins since most of the literature mentions conventional flowable composite resins. Therefore, the present work aimed to exclusively review the bonding behavior to enamel and dentin of self-adhesive flowable composite resins compared to conventional flowable composite resin. A literature search was carried out from 2010 to 2021 in the Pubmed database. The search term used was “self-adhering flowable composite”, where 61 complete articles were evaluated and only 11 were selected. Only studies that evaluated the bond strength by the shear or micro shear test of the self-adhesive fluid composite resin applied to the tooth structure were eligible for selection. Based on this systematic review, it is concluded that the self-adhesive flowable resin demonstrated lower bond strength values to enamel and dentin than conventional flowable resin. The combination of the total acid etch adhesive system with self-adhesive fluid resin showed higher bond strength values than the use of self-adhesives alone. The self-adhesive fluid resin obtained bond strength values similar to glass ionomer-based restorative materials.